Using Participatory Action Research to Support Knowledge Translation in Practice Settings - Wimpenny, Katherine (International Journal of Practice-based Learning in Health and Social Care, 2016)
Health care practitioners must underpin their practice with sound scientific evidence. Yet realising this is not straightforward, especially in light of the amount and appropriateness of research evidence available and its relationship to practice, coupled with practitioners’ own ideology about the contribution of propositional knowledge (the use of propositions, ideas and theories). Knowledge translation is a collaborative means of making the best use of knowledge resulting from theory, policy and research evidence to ensure delivery of best practice to clients and carers to improve health outcomes. This paper presents participatory action research (PAR) as a methodology to meet the challenge of engaging professional staff in knowledge translation to support practice demands through a considered process of reflection, dialogue and action with others. Insights demonstrating PAR methods and results for knowledge translation will be drawn from the literature and from first-hand experience of a professional practice development research project involving occupational therapists working across a health and academic setting in the United Kingdom (UK). The principles and practice of PAR methodology, including a brief history of its purpose and development, are examined. Strategies for ‘getting going’, including consideration of research participant roles, examination of authentic participation and the process of analysis or meaning making are discussed. The overall aim of the paper is to illustrate how PAR might usefully be applied in practice settings to support knowledge translation.